Necrotizing pneumonia in children: Chest computed tomography vs. lung ultrasound - Carrard, Johann; Bacher, Sebastien; Rochat-Guignard, Isabelle; Knebel, Jean-François; Alamo, Leonor; Meuwly, Jean-Yves; Tenisch, Estelle (Frontiers in Pediatrics, 2022)
Background The utiliation of contrast-enhanced computed tomography of the chest (CT) for the diagnosis of necrotizing pneumonia (NP), a complication of community-acquired pneumonia, is controversial because of the inherent ionizing radiation involved. Over the last few years, the growing availability of bedside Lung Ultrasound (LUS) devices has led to increased use of this non-ionizing imaging method for diagnosing thoracic pathology, including pneumonia. Objective The objectives of the present study were: first, to compare the performance of LUS vs CT in the identification of certain radiologic signs of NP and second, to determine whether LUS could replace CT in the diagnosis of NP. Materials and Methods We compared retrospectively the CT and LUS images of 41 patients between 2005 and 2018 in whom at least one contrast injected chest CT scan and one LUS had been undertaken fewer than 7 days apart. Results Pleural effusions were demonstrated almost systematically (100% on CT vs 95.8% on LUS). Visualization of septations in pleural effusions was clearly superior on LUS (20.4% on CT vs 62.5% on LUS). Concerning the detection of necrosis, we observed a strong correlation between LUS and the gold standard CT (95.8% on LUS vs 93.7% on CT). Parenchymal cavities were more easily detected on CT than on LUS (79.1% vs 35.4%). Conclusion LUS has shown to be as effective as CT in the diagnosis of NP. The use of CT in patients with NP could be limited to the detection of complications such as bronchopleural fistulae in unfavorably evolving diseases.